2D Copper Tetrahydroxyquinone Conductive Metal–Organic Framework for Selective CO2 Electrocatalysis at Low Overpotentials. Issue 10 (1st February 2021) - Majidi, Leily; Ahmadiparidari, Alireza; Shan, Nannan; Misal, Saurabh N.; Kumar, Khagesh; Huang, Zhehao; Rastegar, Sina; Hemmat, Zahra; Zou, Xiaodong; Zapol, Peter; Cabana, Jordi; Curtiss, Larry A.; et al.
Abstract: Metal–organic frameworks (MOFs) are promising materials for electrocatalysis; however, lack of electrical conductivity in the majority of existing MOFs limits their effective utilization in the field. Herein, an excellent catalytic activity of a 2D copper (Cu)‐based conductive MOF, copper tetrahydroxyquinone (CuTHQ), is reported for aqueous CO2 reduction reaction (CO2 RR) at low overpotentials. It is revealed that CuTHQ nanoflakes (NFs) with an average lateral size of 140 nm exhibit a negligible overpotential of 16 mV for the activation of this reaction, a high current density of ≈173 mA cm −2 at −0.45 V versus RHE, an average Faradaic efficiency (F.E.) of ≈91% toward CO production, and a remarkable turnover frequency as high as ≈20.82 s −1 . In the low overpotential range, the obtained CO formation current density is more than 35 and 25 times higher compared to state‐of‐the‐art MOF and MOF‐derived catalysts, respectively. The operando Cu K‐edge X‐ray absorption near edge spectroscopy and density functional theory calculations reveal the existence of reduced Cu (Cu + ) during CO2 RR which reversibly returns to Cu 2+ after the reaction. The outstanding CO2 catalytic functionality of conductive MOFs (c‐MOFs) can open a way toward high‐energy‐density electrochemical systems. Abstract : The catalytic performance of a 2D copper tetrahydroxyquinone conductive metal–organic framework (c‐MOF) is studied in the CO2 reduction reaction. In the low overpotential range, the c‐MOF catalyst delivers record values of turn‐over number for CO formation and a negligible overpotential for the CO2 reduction reaction. These findings open a new path for further advances in core electrochemical reactions.